2007
DOI: 10.1016/j.devcel.2007.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Apelin and Its Receptor Control Heart Field Formation during Zebrafish Gastrulation

Abstract: The vertebrate heart arises during gastrulation as cardiac precursors converge from the lateral plate mesoderm territories toward the embryonic midline and extend rostrally to form bilateral heart fields. G protein-coupled receptors (GPCRs) mediate functions of the nervous and immune systems; however, their roles in gastrulation remain largely unexplored. Here, we show that the zebrafish homologs of the Agtrl1b receptor and its ligand, Apelin, implicated in physiology and angiogenesis, control heart field form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
188
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(207 citation statements)
references
References 43 publications
(56 reference statements)
16
188
0
3
Order By: Relevance
“…Loss of Apela in zebrafish results in embryonic death, with the mutant embryos manifesting failure of heart formation, posterior accumulation of blood cells, malformation of pharyngeal endoderm, and abnormal left-right positioning and formation of the liver. The similarity of the phenotypes of Apela-deficient embryos to those of Aplnr mutants (Scott et al, 2007;Zeng et al, 2007) validates the function of Apela as the agonist for Aplnr (Fig. 3C).…”
Section: (3) Apelamentioning
confidence: 85%
“…Loss of Apela in zebrafish results in embryonic death, with the mutant embryos manifesting failure of heart formation, posterior accumulation of blood cells, malformation of pharyngeal endoderm, and abnormal left-right positioning and formation of the liver. The similarity of the phenotypes of Apela-deficient embryos to those of Aplnr mutants (Scott et al, 2007;Zeng et al, 2007) validates the function of Apela as the agonist for Aplnr (Fig. 3C).…”
Section: (3) Apelamentioning
confidence: 85%
“…In fish, AT 1 receptors have been identified in several species, including eel, Anguilla anguilla; toadfish, Opsanus beta; and rainbow trout, Oncorhynchus mykiss (Nishimura 2001). Although Tucker et al (2007) reported the presence of putative AT 1 receptors in zebrafish, there is debate as to whether the ligand for this receptor is actually apelin rather than ANG-II (Zeng et al 2007). Based on immunohistochemical staining with a mouse MAB, the AT 1 receptor was localised to osmoregulatory tissues, including ionocytes from eel gill (for review, see Nishimura (2001) and Russell et al (2001)).…”
Section: Discussionmentioning
confidence: 99%
“…Recently the apelinergic system has been described to promote embryonic and tumor angiogenesis [19,9,43]. Growing evidences of apelin/APJ involvement in embryonic events currently extend beyond vascular development, into ocular [20] and heart development [42,49,14].…”
Section: Introductionmentioning
confidence: 99%